2018
DOI: 10.1007/s13762-018-2143-7
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and health risk assessment of phthalate esters in household’s drinking water of Isfahan, Iran

Abstract: This study aimed to determine the presence of phthalates and their concentration in household's drinking water and to examine their potential risk for inhabitants in urban regions of Isfahan, Iran. During the summer and winter of 2017, samples were extracted from 33 private residences via dispersive liquid-liquid microextraction with some modifications. Gas chromatography-mass spectrometry was used to determine the presence of four major phthalates. According to the results, four phthalates, including dibutyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…The DR values of 10 chemical compounds in the influent were more than 50%, including Ba (99.3%), dibutyl phthalate (92.1%), dioctyl phthalate (91.4%), polychlorinated biphenyls (81.4%), di(2-ethylhexyl) adipate (59.3%), trichlorobenzene (57.9%), dichloromethane (55.0%), dichloromethane (53.6%), microcystin-LR (50.7%), and 1,2-dichloroethane (50.7%). The results suggested that these pollutants were widely distributed, which were consistent with their global distributions [18,30,31]. More detailed informations were provided in Additional file 1: Tables S3 and S4.…”
Section: Distribution Of Chemical Compoundssupporting
confidence: 68%
“…The DR values of 10 chemical compounds in the influent were more than 50%, including Ba (99.3%), dibutyl phthalate (92.1%), dioctyl phthalate (91.4%), polychlorinated biphenyls (81.4%), di(2-ethylhexyl) adipate (59.3%), trichlorobenzene (57.9%), dichloromethane (55.0%), dichloromethane (53.6%), microcystin-LR (50.7%), and 1,2-dichloroethane (50.7%). The results suggested that these pollutants were widely distributed, which were consistent with their global distributions [18,30,31]. More detailed informations were provided in Additional file 1: Tables S3 and S4.…”
Section: Distribution Of Chemical Compoundssupporting
confidence: 68%
“…Our result is in agreement with previous studies [ 13 , 29 ], where PAEs were not observed to pose a health risk to humans via exposure through surface water. Nevertheless, many studies have reported that some PAEs are environmentally active endocrine-disrupting pollutants, which can cause toxic and cancer effects at very low concentrations [ 60 , 61 , 62 , 63 , 64 , 65 ]. Although exposure to PAEs in our study was safe in terms of toxic (noncarcinogenic) and carcinogenic effects, assessment of contaminants from other sources, including indoor and outdoor air, cosmetics, drinking water, and food, is essential for determining the actual cumulative exposure [ 13 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, many studies have reported that some PAEs are environmentally active endocrine-disrupting pollutants, which can cause toxic and cancer effects at very low concentrations [60][61][62][63][64][65]. Although exposure to PAEs in our study was safe in terms of toxic (noncarcinogenic) and carcinogenic effects, assessment of contaminants from other sources, including indoor and outdoor air, cosmetics, drinking water, and food, is essential for determining the actual cumulative exposure [13,60]. Besides, the risk assessment approach used in this present study is only a deterministic approach, which presented a quantitative estimation of the human health risk.…”
Section: Human Health Riskmentioning
confidence: 99%
“…Currently, phthalate exposure via diet, indoor dust, drinking water, personal care products and medicine are the most studied. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%